Who's who in contemporary women's writing - Miller,Jane Edridge (Routledge, 2001)
Who's Who in Contemporary Women's Writing is a comprehensive, authoritative and enjoyable guide to women's fiction, prose, poetry and drama from around the world in the second half of the twentieth century